Game CARRE (Cardiac Arrest) sebagai Upaya Peningkatan Bystander Resusitasi Jantung Paru (RJP): Development and Usability Study - Guruh Wirasakti; Yunita Wahyu Wulansari; Feri Ekaprasetia (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2022)
Background: The prevalence of out-of-hospital cardiac arrest is increasing every year and must be balanced with an increase in bystanders as first aid for victims of cardiac arrest. School-age children can be the first person who find victims of cardiac arrest, so it is necessary to increase bystander CPR in school-age children. Purpose: developed the “CARRE (cardiac arrest) Game” as an educational application for junior high school children Method: This study uses a quantitative approach to the application of CARRE (cardiac arrest) Game involving 50 junior high school students in Jember Regency. This application is developed in three stages, the first stage is the development of an android game-based application. Content creation is the second stage in the development of the Game CARRE (Cardiac Arrest) application. The third part conducts expert tests on nursing lecturers with emergency science, emergency science nurses, and information systems experts. Results: Based on the reliability evaluator value test (single measure) using Intraclass correlation, it shows a value of 0.727, which means that the developed application has a good reliability coefficient. Furthermore, from the feasibility test on 50 respondents stated that 85% of the applications were declared very feasible. Conclusion: The development of the CAREE Game application based on an android game as education about cardiac arrest and its handling with CPR is very appropriate to be used as an effort to increase CPR bystander in school-age children.